Entrepreneurship Dan Strategi Bisnis Dalam Islam (Overview QS. Quraisy: 1-4) - Dwiatmaja, Ahmad Zikri; Halimah Basri; Muhammad Daming (BISMA : Business and Management Journal, 2024)
This research aims to find out the literature related to entrepreneurship principles and business strategies contained in Surah Quraysh. The research method used in the study is literature analysis, which is also known as literature study. The results of the research show that Surah Quraysh provides a strong foundation for the development of sharia-based business strategies. The example of the Prophet Muhammad (SAW) contained in Surah Quraysh such as developing a coherent business strategy, perseverance, learning, and habituation, then social care that provides a strong ethical foundation for entrepreneurs who want to run a business in accordance with Islamic values. It also encourages social responsibility, concern for society, and integrity in business. By referring to the principles of entrepreneurship in Surah Quraysh, entrepreneurs can build business strategies that are sustainable, ethical and beneficial to society, while gaining blessings in their endeavors. Seeing the example of the Prophet Muhammad SAW. in entrepreneurship and business teaches that forming a sharia business foundation that is in accordance with Islamic values and is oriented towards justice, blessings and sustainability. The business strategy contained in Surah Al-Quraisy verses 1 - 4 is perseverance, learning and habituation from small, Brand Equity and Master Brand, outward expansion, building networks, as well as diplomacy and negotiation skills, market segmentation, balance between business and worship, tawakkal accompanied by hard work.